Growth of lactic acid bacteria and yeast in the mixed and monoculture culture on natural substrate (Experimental biology, 2016)
In this research the strains of cultured lactic acid bacteria and yeast on natural sustrate - whey. The objects were selected strains of lactic acid bacteria isolated from natural sources - Lactobacillus acidophilus AK-17, Lactobacillus plantarum AP-17, yeast - Torulopsis kefir T-17 and Rhodotorula glutinis. It was investigated the patterns of growth of mono- and mixed cultures of microorganisms adapted to the whey. The activity of acid forming and intensity of accumulation of biomass cultures as a result of selected active strains and variants of mixed cultures. Were studied intensive growth was detected from cell variants of mixed cultures with different groups of lactic acid bacteria. 3 and 5 variants including strong acid-forming Lactobacillus acidophilus strain AK-17, provide the greatest increase in cells. Studies have shown that the most optimal for feed protein are mixed cultures containing lactic acid bacteria and yeast. They provide the greatest increase in cells, and thus the protein.
Keywords: lactic acid bacteria; yeast; raw material; milk whey Monoculture; mixed culture.